Manufacturing method of superabsorbent resin
By controlling the heat treatment temperature conditions during the surface crosslinking stage of the superabsorbent resin, the problems of differences in centrifugal separation of superabsorbent resin particles and unstable water retention capacity are solved, and the absorption performance of the product is significantly improved.
Patent Information
- Application Number
- JP2023541998
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-08
- Filing Date
- 2022-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-09
AI Technical Summary
When producing superabsorbent resins, insufficient control of the temperature conditions of the surface cross-linking treatment leads to differences in centrifugal separation of superabsorbent resin particles and unstable water retention capacity, which in turn affects the absorption performance of the final product.
Optimize equipment temperature management during surface crosslinking by controlling the heat treatment temperature conditions during the surface crosslinking phase to ensure that the temperature range of the crosslinking reaction remains at 10°C to 20°C for a specific time period.
It effectively reduces the difference in centrifugal separation of superabsorbent resin particles and the instability of water retention capabilities, and improves the absorption performance and physical properties of the final product.
Smart Images

Figure 0007648287000002 
Figure 0007648287000003 
Figure 0007648287000001
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0177007 dated December 10, 2021 and Korean Patent Application No. 10-2022-0170466 dated December 8, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a method for producing a superabsorbent resin, more particularly, to a method for producing a superabsorbent resin, which reduces the deviation in centrifugal water retention capacity of the superabsorbent resin particles produced by controlling the heat treatment temperature conditions in the surface crosslinking step, thereby improving the absorption properties of the superabsorbent resin finally produced. [Background technology]
[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that can absorb 500 to 1,000 times its own weight in water, and is given different names by different developers, such as SAM (Super Absorbency Material) and AGM (Absorbent Gel Material). Such super absorbent polymers first came into practical use as sanitary products, and are now widely used as soil water retention agents for horticulture, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents in the food distribution field, and materials for poultices.
[0004] Such superabsorbent polymers are widely used in the field of sanitary materials, such as diapers and sanitary napkins. In the sanitary materials, the superabsorbent polymers are generally contained in a state of being spread in the pulp. However, in recent years, efforts have been made to provide sanitary materials, such as diapers, with thinner thicknesses, and as part of these efforts, the development of so-called pulpless diapers, which contain less pulp or even no pulp at all, has been actively promoted.
[0005] In this way, in the case of sanitary materials in which the pulp content is reduced or no pulp is used, the superabsorbent polymer is contained at a relatively high ratio, and the superabsorbent polymer particles are inevitably contained in multiple layers in the sanitary material. In order for the overall superabsorbent polymer particles contained in multiple layers in this way to more efficiently absorb a large amount of liquid such as urine, the superabsorbent polymer basically needs to exhibit not only high absorption performance but also fast absorption speed.
[0006] Meanwhile, in order to obtain a superabsorbent resin having excellent physical properties, various attempts have been made to subject the resin powder obtained in the polymerization, pulverization, drying and final pulverization steps to surface treatment, or to improve the efficiency of the polymerization, pulverization and drying steps.
[0007] In the case of such a surface cross-linking process, the properties of the water-absorbent resin particles produced vary depending on the operating conditions in the device, and when the deviation in the absorption properties becomes large, it is difficult to obtain a high water-absorbent resin of the desired quality. Therefore, research is required to optimize the operating conditions of the surface cross-linking process. Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, the present invention provides a method for producing a superabsorbent resin, which reduces the deviation in the centrifugal water retention capacity of the produced superabsorbent resin particles by controlling the heat treatment temperature conditions in the surface crosslinking step, and improves the absorption properties of the final superabsorbent resin. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides Step 1: cross-linking an acrylic acid monomer having at least a partially neutralized acid group in the presence of an internal cross-linking agent to form a hydrogel polymer; (Step 2) drying, pulverizing and classifying the hydrogel polymer to obtain a base resin powder; and (3) heat-treating the base resin powder in the presence of a surface cross-linking agent to prepare highly water-absorbent resin particles having a surface cross-linked layer formed thereon, The surface cross-linking of step 3 is carried out by increasing the temperature to a target temperature (T), The method for producing a superabsorbent resin in step 3 is provided, in which the difference between the temperature (T1) at the time when 25% to 40% of the total surface crosslinking time has elapsed and the temperature (T2) at the time when 70% to 100% has elapsed is 10°C to 20°C. Effect of the Invention
[0010] According to the method for producing a superabsorbent resin of the present invention, by controlling the heat treatment temperature conditions in the surface crosslinking step, it is possible to reduce the deviation in the centrifugal water retention capacity of the produced superabsorbent resin particles, and to produce a superabsorbent resin having improved absorption properties of the final superabsorbent resin. [Brief description of the drawings]
[0011] [Figure 1] 1 is a graph showing measured values of CRC according to surface crosslinking reaction time in Examples and Comparative Examples of the present invention. [Diagram 2] 1 is a graph showing AUP values with respect to CRC by surface crosslinking reaction time period in Examples and Comparative Examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention.
[0013] The singular term includes the plural term unless the context clearly indicates otherwise. In this specification, the terms "comprise", "comprise", "have" or the like are intended to specify the presence of embodied features, steps, components, or combinations thereof, and should be understood as not precluding the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.
[0014] Although the terms first, second, third, etc. may be used to describe various components, such terms are only used to distinguish one component from another.
[0015] Since the present invention can be modified in various ways and can have various forms, specific examples are exemplified and described in detail below, but it is not intended to limit the present invention to the specific disclosed form, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.
[0016] The term "polymer" or "polymeric polymer" as used herein means a state in which acrylic acid monomers are polymerized, and may include all ranges of water content or particle size. Among the above polymers, polymers having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying are called hydrogel polymers, and particles of such hydrogel polymers that are crushed and dried are called crosslinked polymers.
[0017] In addition, the term "superabsorbent resin particles" refers to a particulate material that contains acidic groups and includes a crosslinked polymer formed by polymerizing an acrylic acid monomer in which at least a portion of the acidic groups have been neutralized and crosslinked by an internal crosslinking agent.
[0018] In addition, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of the acidic groups being neutralized, or a powder-type base resin formed by pulverizing the crosslinked polymer, or refers to any of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, pulverization into fine powder, drying, pulverization, classification, etc., to be suitable for commercialization, depending on the context.
[0019] In addition, the term "crosslinked polymer" means a product crosslinked and polymerized in the presence of the acrylic acid-based monomer and an internal crosslinking agent, and the term "base resin particles" means a particulate (powdered) material containing such a crosslinked polymer.
[0020] A method for producing a superabsorbent resin according to an embodiment of the present invention includes a step (step 1) of cross-linking an acrylic acid monomer having at least a partially neutralized acid group in the presence of an internal cross-linking agent to form a hydrogel polymer, a step (step 2) of drying, pulverizing and classifying the hydrogel polymer to obtain a base resin powder, and a step (step 3) of heat-treating the base resin powder in the presence of a surface cross-linking agent to produce superabsorbent resin particles having a surface cross-linked layer formed thereon, wherein the surface cross-linking in step 3 is performed by increasing the temperature to a target temperature (T), and the difference between the temperature (T1) at the time when 25% to 40% of the total time for performing the surface cross-linking in step 3 has elapsed and the temperature (T2) at the time when 70% to 100% has elapsed is 10°C to 20°C.
[0021] In the past, in order to improve the absorption properties of superabsorbent resins, research has been conducted to improve the absorption properties by performing a heat treatment process in the presence of a surface crosslinking agent and adjusting the components of the surface crosslinking agent and other additives used.
[0022] However, in the case of such a surface cross-linking step, the physical properties of the water absorbent resin particles produced are different depending on the driving conditions in the device as well as the surface cross-linking component, and this has caused a problem that it is difficult to uniformly obtain a high water absorbent resin of a desired quality.
[0023] Therefore, the present inventors optimized the operating conditions of the surface crosslinking process, specifically, analyzed the influence of the residence time of the base resin powder at each temperature in an apparatus where the surface crosslinking reaction is performed in the surface crosslinking step performed at an elevated temperature, and confirmed that when the deviation in the temperature range at a specific point in time is controlled, the deviation in the centrifugal water retention capacity of the produced superabsorbent resin particles can be effectively reduced, thereby completing the present invention.
[0024] The highly absorbent polymer produced according to the present invention can achieve excellent absorbent properties, and in particular has excellent effective water absorption capacity.
[0025] Hereinafter, each step of the method for producing a superabsorbent resin according to an embodiment of the present invention will be described in detail.
[0026] (Step 1: Polymerization Step) A method for preparing a superabsorbent resin according to one embodiment of the present invention includes a step (step 1) of cross-linking an acrylic acid monomer having at least a partially neutralized acid group in the presence of an internal cross-linking agent to form a hydrogel polymer.
[0027] The polymerization step is a step of forming a hydrogel polymer by photopolymerizing and / or thermally polymerizing a monomer composition including an acrylic acid monomer having at least a partially neutralized acid group in the presence of an internal crosslinking agent.
[0028] First, a monomer mixture containing an acrylic acid monomer having at least a partially neutralized acid group is prepared in the presence of an internal crosslinking agent, and the monomer mixture may further contain a polymerization initiator for polymerization.
[0029] The acrylic acid monomer may be any monomer commonly used in the manufacture of superabsorbent resins. As a non-limiting example, the acrylic acid monomer may be a compound represented by the following Formula 1:
[0030] [Chemical formula 1] R1-COOM 1
[0031] In the above Chemical Formula 1, R1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0032] Preferably, the acrylic acid monomer may be one or more selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts of these acids. When an acrylic acid monomer is used in this way, it is advantageous to obtain a highly water-absorbent resin having improved water absorption. In addition, the monomer may be at least one selected from the group consisting of anionic monomers of maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, or 2-(meth)acrylamido-2-methylpropanesulfonic acid, and their salts; nonionic hydrophilic monomers of (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, or polyethylene glycol (meth)acrylate; and amino group-containing unsaturated monomers of (N,N)-dimethylaminoethyl (meth)acrylate or (N,N)-dimethylaminopropyl (meth)acrylamide, and their quaternized products.
[0033] Here, the acrylic acid monomer has an acidic group, and at least a part of the acidic group is partially neutralized using a neutralizing solution. At this time, the neutralizing agent contained in the neutralizing solution may be a basic substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide capable of neutralizing the acidic group.
[0034] At this time, the neutralization degree of the monomer may be 40 to 95 mol%, or 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree varies depending on the final properties, but if the neutralization degree is too high, the neutralized monomer precipitates and the polymerization is not smoothly carried out, and conversely, if the neutralization degree is too low, the water absorption of the polymer is greatly reduced and the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.
[0035] The term "internal crosslinking agent" used in this specification is used to distinguish it from the "surface crosslinking agent" for crosslinking the surface of the base resin, and plays a role in crosslinking the unsaturated bonds of the above-mentioned acrylic acid monomer to polymerize. The crosslinking in this step is performed without distinction between the surface and the inside, but the surface of the superabsorbent resin particles finally produced by the surface crosslinking process of the base resin described below has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.
[0036] The internal crosslinking agent may be a polyfunctional component, and for example, one or more selected from the group consisting of N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerin, and ethylene carbonate may be used. Preferably, polyethylene glycol di(meth)acrylate or propylene glycol di(meth)acrylate can be used.
[0037] The internal crosslinking agent can be used in an amount of 100 ppmw to 10,000 ppmw based on the weight of the acrylic acid monomer. When the content is within this range, sufficient crosslinking can be used to achieve strength above an appropriate level, and sufficient water retention can be achieved by introducing an appropriate crosslinking structure. Preferably, the content is 100 ppmw or more, 200 ppmw or more, 300 ppmw or more, or 600 ppmw or more, and 10,000 ppmw or less, 9,000 ppmw or less, 7,000 ppmw or less, or 5,000 ppmw or less, and is included in an amount of 200 ppmw to 9,000 ppmw, 300 ppmw to 7,000 ppmw, or 600 ppmw to 5,000 ppmw. If the content of the internal crosslinking agent is too low, crosslinking does not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density increases, making it difficult to achieve the desired water retention.
[0038] The polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator depending on the polymerization method, but a thermal polymerization initiator is also used since a certain amount of heat is generated by UV irradiation and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, even in the photopolymerization method.
[0039] Here, the photopolymerization initiator may be, for example, one or more compounds selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkylketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Specific examples of acylphosphine include commercially available lucirin TPO, i.e., 2,4,6-trimethyl-benzoyl-trimethyl-phosphine oxide, and diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide. A wider variety of photoinitiators are well described in "UV Coatings: Basics, Recent Developments and New Applications" by Reinhold Schwalm (Elsevier, 2007), p. 115, and are not limited to the examples mentioned above.
[0040] The thermal polymerization initiator may be one or more compounds selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid.Specific examples of the persulfate initiator include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), A wide variety of thermal polymerization initiators are disclosed in Odian's book "Principle of Polymerization (Wiley, 1981)" p. 203, and are not limited to the above examples.
[0041] Such a polymerization initiator is used at 10 ppmw to 10,000 ppmw based on the weight of the acrylic acid monomer. Preferably, it is 10 ppmw or more, 30 ppmw or more, 50 ppmw or more, and 10,000 ppmw or less, 5,000 ppmw or less, or 3,000 ppmw or less, and is contained at 30 ppmw to 5,000 ppmw, 50 ppmw to 3,000 ppmw, or 80 ppmw to 2,500 ppmw. If the concentration of the polymerization initiator is too low, the polymerization rate is slowed down and a large amount of residual monomer is extracted in the final product, which is not preferable. On the other hand, if the concentration of the polymerization initiator is too high, the polymer chain forming the network is shortened, the content of water-soluble components is increased, and the pressurized absorption capacity is reduced, which is not preferable, and the physical properties of the resin may be reduced. The content of the polymerization initiator means the combined content when a photopolymerization initiator and a thermal polymerization initiator are used together.
[0042] In addition, the monomer composition may further contain additives such as a foaming agent, a surfactant, a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0043] The foaming agent plays a role of increasing the surface area by forming pores in the hydrogel polymer as foaming occurs during polymerization. The foaming agent may be a carbonate, and examples thereof include sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate.
[0044] In addition, the foaming agent is preferably used in an amount of 1500 ppmw or less based on the weight of the water-soluble ethylenically unsaturated monomer. If the amount of foaming agent used exceeds 1500 ppmw, the pores may become excessively large, the gel strength of the superabsorbent resin may decrease, and the density may decrease, which may cause problems in distribution and storage. In addition, the foaming agent is preferably used in an amount of 500 ppmw or more, or 1000 ppmw or more based on the weight of the water-soluble ethylenically unsaturated monomer.
[0045] The surfactant induces uniform dispersion of the foaming agent, and prevents the gel strength or density from decreasing due to uniform foaming during foaming. It is preferable to use an anionic surfactant as the surfactant. Specifically, the surfactant is SO3 - The compound containing an anion and represented by the following chemical formula 2 can be used.
[0046] [Chemical formula 2] R-SO3Na
[0047] In the above Chemical Formula 2, R is an alkyl group having 8 to 16 carbon atoms.
[0048] The surfactant is preferably used in an amount of 300 ppmw or less based on the weight of the acrylic acid monomer. If the amount of the surfactant used exceeds 300 ppmw, the content of the surfactant in the superabsorbent resin increases, which is not preferable. The surfactant is preferably used in an amount of 100 ppmw or more, or 150 ppmw or more based on the weight of the water-soluble ethylenically unsaturated monomer.
[0049] The monomer composition is prepared in the form of a solution in which raw materials such as the monomer, the internal crosslinking agent, the foaming agent, and the initiator are dissolved in a solvent.
[0050] In this case, the solvent that can be used is not limited in composition as long as it can dissolve the above-mentioned raw materials. For example, the solvent may be water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, or a mixture thereof.
[0051] The step of forming the hydrogel polymer by polymerizing the monomer composition is carried out by a conventional polymerization method, and the process is not particularly limited. As a non-limiting example, it can be carried out in a reactor equipped with a movable conveyor belt.
[0052] Specifically, when the photopolymerization of the monomer composition is carried out in a reactor equipped with a movable conveyor belt, a sheet-like hydrogel polymer is obtained. At this time, the thickness of the sheet varies depending on the concentration and injection speed of the monomer composition to be injected, but it is usually preferable to adjust the thickness to 0.5 to 10 cm in order to ensure the production speed while allowing the entire sheet to be polymerized uniformly.
[0053] The water content of the hydrogel polymer obtained by such a method may be 40% to 80% by weight. Meanwhile, throughout this specification, the term "water content" refers to the water content relative to the total weight of the hydrogel polymer, and means the weight of the hydrogel polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer by infrared heating. At this time, the drying conditions are a method of increasing the temperature from room temperature to 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase step, and the water content is measured.
[0054] (Step 2: Drying, grinding and classification step) Next, the hydrogel polymer is dried, pulverized and classified to obtain a base resin powder (Step 2).
[0055] Specifically, the obtained hydrogel polymer is dried. If necessary, the hydrogel polymer may be coarsely pulverized before drying in order to increase the efficiency of the drying step.
[0056] In this case, the crusher used is not limited in configuration, and specifically may include any one selected from the group of crushing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.
[0057] In this case, the coarse pulverization step can be performed so that the hydrogel polymer has a particle size of 2 to 10 mm. It is technically difficult to pulverize the hydrogel polymer to a particle size of less than 2 mm due to the high water content of the hydrogel polymer, and the pulverized particles may aggregate with each other. On the other hand, if the hydrogel polymer is pulverized to a particle size of more than 10 mm, the efficiency of the subsequent drying step is reduced.
[0058] The hydrogel polymer immediately after polymerization, which has been coarsely pulverized as described above or has not been subjected to the coarse pulverization step, is dried. At this time, the drying temperature in the drying step may be 150 to 250°C. If the drying temperature is less than 150°C, the drying time becomes too long, and the physical properties of the superabsorbent resin finally formed may be deteriorated, and if the drying temperature exceeds 250°C, only the surface of the polymer may be excessively dried, and fine powder may be generated in the subsequent pulverization step, and the physical properties of the superabsorbent resin finally formed may be deteriorated. Therefore, the drying is preferably performed at a temperature of 150 to 200°C, more preferably at a temperature of 170 to 195°C.
[0059] Meanwhile, the drying time is 20 to 90 minutes in consideration of process efficiency, but is not limited thereto.
[0060] The drying method in the drying step can be selected and used without any limitation on the configuration as long as it is one that is usually used in the drying process of a hydrogel polymer. Specifically, the drying step can be carried out by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after such a drying step may be about 0.1 to about 10% by weight.
[0061] Next, the dried polymer obtained through such a drying step is subjected to a pulverization step.
[0062] The polymer-based resin powder obtained after the pulverization step may have a particle size of 150 to 850 μm. Specifically, the pulverizer used for pulverizing to such a particle size may be a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill, but is not limited to the above examples.
[0063] After the pulverization step, the base resin powder obtained after pulverization may be classified according to particle size in order to control the physical properties of the superabsorbent resin particles to be manufactured into a final product. Preferably, the polymer having a particle size of 150 to 850 μm is classified, and only the particles having such a particle size are subjected to a surface crosslinking reaction step to manufacture the product. More specifically, the classified base resin powder may have a particle size of 150 to 850 μm and contain 50% by weight or more of particles having a particle size of 300 to 600 μm.
[0064] Meanwhile, fines having a particle size of less than 150 μm may be generated during the polymerization, drying and pulverization steps. The fines having a particle size of less than 150 μm classified during the above classification step can be re-granulated into normal particles having a particle size of 150 μm or more, and recycled as base resin powder.
[0065] The regranulation process of the fine powder may be carried out by a method commonly used in the art, for example, by a process of agglomerating the fine powder in a wet state. Specifically, the classified fine powder may be mixed with water to agglomerate it, and then the water may be dried in a re-drying process to produce normal particles. In the regranulation process, additives such as water-soluble polymers may be selectively used to improve the agglomeration strength of the particles.
[0066] (Step 3: Surface cross-linking step) Next, the method for preparing a superabsorbent resin according to one embodiment of the present invention includes a step (step 3) of heat-treating the base resin powder in the presence of a surface cross-linking agent to prepare superabsorbent resin particles having a surface cross-linked layer.
[0067] The surface cross-linking step induces a cross-linking reaction on the surface of the base resin powder in the presence of a surface cross-linking agent, and the unsaturated bonds of the acrylic acid monomer remaining on the surface without being cross-linked are cross-linked by the surface cross-linking agent, forming a superabsorbent resin with a high surface cross-linking density.
[0068] Specifically, a surface cross-linked layer can be formed by a heat treatment process in the presence of a surface cross-linking agent. The heat treatment process increases the surface cross-linking density, i.e., the external cross-linking density, while the internal cross-linking density does not change. Therefore, the produced superabsorbent resin having a surface cross-linked layer has a structure in which the external cross-linking density is higher than the internal cross-linking density.
[0069] The present inventors optimized the surface crosslinking process conditions, analyzed the influence of the residence time of the base resin powder at each temperature in an apparatus where the surface crosslinking reaction is performed, and confirmed that the deviation in the centrifugal water retention capacity of the produced superabsorbent resin particles can be effectively reduced by controlling the deviation in the temperature range at a specific time point, thereby completing the present invention.
[0070] The surface crosslinking in step 3 is performed by increasing the temperature to a target temperature, and if a temperature reduction condition is included in the surface crosslinking step, the surface crosslinking reaction rate is reduced, and the absorbency under pressure (AUP) is reduced. In addition, in this specification, increasing the temperature to a target temperature may include gradually increasing the temperature and maintaining it at the target temperature.
[0071] The target temperature (T) of the surface crosslinking is 170°C to 190°C, and the "target temperature" here means the maximum reaction temperature of the heat treatment. Therefore, the surface crosslinking is performed while increasing the temperature to the maximum reaction temperature. The target temperature may be preferably 179°C to 195°C, 179°C to 187°C, or 182°C to 187°C. By satisfying such surface crosslinking process conditions (particularly, the temperature increase conditions and the reaction conditions at the maximum reaction temperature), a highly water-absorbent resin that appropriately satisfies physical properties such as more excellent effective water absorption capacity can be produced.
[0072] The surface cross-linking step of step 3 is performed by controlling the difference (T2-T1) between the temperature (T1) at the time when 25%-40% of the total surface cross-linking time has elapsed and the temperature (T2) at the time when 70%-100% has elapsed, to 10° C.-20° C. By satisfying the above-mentioned temperature deviation, the deviation in the centrifugal water retention capacity of the produced superabsorbent resin particles can be effectively reduced.
[0073] Preferably, the surface crosslinking step is performed by controlling the difference (T2-T1) between the temperature (T1) at the time when 30%-40% of the total surface crosslinking time has elapsed and the temperature (T2) at the time when 90%-100% has elapsed, to 10°C-20°C.
[0074] If the temperature difference exceeds 20° C., a deviation in water retention occurs between particles of the superabsorbent resin produced. On the other hand, if the temperature difference is less than 10° C., the surface cross-linking does not proceed smoothly, resulting in a very low AUP, or a rapid temperature rise causes a rapid change in the CRC fluctuation range, resulting in a deterioration in physical properties.
[0075] The difference (T2-T1) in the heat treatment temperature in the surface crosslinking stage is preferably 10° C. to 17° C. or 12° C. to 17° C., and within this range, the above-mentioned problems do not occur, which is preferable.
[0076] The total time for performing the surface crosslinking is 45 to 75 minutes, which means the total time from the time point when the base resin powder and the surface crosslinking agent are mixed to the time point when the temperature is raised to reach the above-mentioned target temperature, maintained at the target temperature, and discharged out of the surface crosslinking reactor. The total time for performing the surface crosslinking is preferably 50 to 60 minutes. Meanwhile, in the examples described later, the target temperature was maintained for a long time in the surface crosslinking reactor in order to monitor the change in the physical properties of the resin according to the change in the temperature of the surface crosslinking.
[0077] On the other hand, the temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but is not limited to these, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, the heat source to be directly supplied can be, but is not limited to the above-mentioned examples, heating by electricity and heating by gas.
[0078] In addition, the reaction device for the surface crosslinking reaction is not particularly limited as long as it is a device capable of carrying out the above-mentioned heat treatment step, and for example, a paddle dryer can be used.
[0079] Meanwhile, as the surface cross-linking agent contained in the surface cross-linking agent composition, any cross-linking agent component that has been used in the manufacture of superabsorbent resins can be used without any particular restrictions.For example, the surface cross-linking agent can include one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; one or more carbonate-based compounds selected from the group consisting of ethylene carbonate and propylene carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; mono-, di- or polyoxazolidinone compounds; or cyclic urea compounds; etc. Preferably, one or more selected from the group consisting of 1,3-propanediol, propylene glycol, 1,4-butanediol, ethylene carbonate, propylene carbonate, and ethylene glycol diglycidyl ether can be used, and more preferably, ethylene carbonate and propylene carbonate are mixed in a ratio of 1:1 and used, or ethylene carbonate can be used alone.
[0080] Such a surface cross-linking agent can be used at a content of 1,000 ppmw to 5,000 ppmw, preferably 1,000 ppmw to 3,000 ppmw or 1,000 ppmw to 2,000 ppmw, based on the base resin powder. By adjusting the content range of the surface cross-linking agent to the above-mentioned range, a highly water-absorbent resin exhibiting various physical properties such as excellent water absorption performance and liquid permeability can be produced.
[0081] Meanwhile, the surface crosslinking agent is added to the base resin powder in the form of a surface crosslinking agent composition containing the surface crosslinking agent, and the method of adding the surface crosslinking agent composition is not particularly limited in its constitution. For example, a method of putting the surface crosslinking agent composition and the base resin powder in a reaction tank and mixing them, a method of spraying the surface crosslinking agent composition on the base resin powder, a method of continuously supplying the base resin and the surface crosslinking agent composition to a continuously operated mixer, and the like can be used.
[0082] The surface crosslinking agent composition may further include water and / or a hydrophilic organic solvent as a solvent. Therefore, there is an advantage that the surface crosslinking agent can be uniformly dispersed on the base resin powder. At this time, the content of water and the hydrophilic organic solvent can be adjusted and applied by controlling the addition ratio with respect to 100 parts by weight of the base resin powder in order to induce uniform dissolution / dispersion of the surface crosslinking agent and prevent the clumping phenomenon of the base resin powder, while optimizing the surface penetration depth of the surface crosslinking agent.
[0083] Meanwhile, in the method for producing a superabsorbent resin according to an embodiment of the present invention, aluminum salts such as aluminum sulfate salts and other various polyvalent metal salts may be further used during surface cross-linking in order to further improve liquid permeability, etc. Such polyvalent metal salts are contained on the surface cross-linked layer of the finally produced superabsorbent resin.
[0084] (Super absorbent resin) The superabsorbent resin produced according to the above-mentioned embodiment may have a particle size of 150 to 850 μm. More specifically, at least 95% by weight of the superabsorbent resin may have a particle size of 150 to 850 μm, and may contain 50% by weight or more of particles having a particle size of 300 to 600 μm, and may contain less than 3% by weight of fine powder having a particle size of less than 150 μm.
[0085] The superabsorbent resin produced according to the above-described embodiment realizes excellent water absorption properties, and in particular, exhibits excellent absorption speed and effective water absorption capacity.
[0086] The superabsorbent resin has a centrifugation retention capacity (CRC) of 40 g / g or more, preferably 40 g / g to 43 g / g, or 40 g / g to 42 g / g, as measured by EDANA method WSP241.2. The method for measuring the centrifugation retention capacity (CRC) will be described in more detail in the experimental examples described later.
[0087] The superabsorbent polymer has an absorbency under pressure (AUP) of 18 g / g to 25 g / g, preferably 19 g / g to 23 g / g, or 19.5 g / g to 23 g / g, at 0.7 psi, as measured by EDANA method WSP242.0.R2. The method for measuring the absorbency under pressure (AUP) will be described in more detail in the experimental examples described later.
[0088] The superabsorbent resin has an effective water absorption capacity (EFFC) calculated by the following formula 1 of 31 / g or more, and preferably 31.2 g / g or more.
[0089] [Formula 1] Effective water absorption capacity (EFFC) = {Water retention capacity (CRC) + Absorbency capacity under 0.7 psi pressure (AUP)} / 2
[0090] The method for measuring the effective water absorption capacity (EFFC) will be described in more detail in the experimental examples described below.
[0091] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these examples are merely presented as examples of the invention and do not define the scope of the invention.
[0092] [Examples and Comparative Examples] Example 1 (Step 1-Polymerization) 484g of acrylic acid, 2,100ppmw (based on acrylic acid monomer) of polyethylene glycol diacrylate (PEGDA 400, Mw=400) as an internal crosslinking agent, and 80ppmw (based on acrylic acid monomer) of diphenyl (2,4,6-trimethylbenzoyl)-phosphine oxide as a photopolymerization initiator were added and dissolved in a 3L glass container equipped with a stirrer and a thermometer, and then 643g of a 31.5% by weight concentration sodium hydroxide solution was added to prepare a water-soluble unsaturated monomer aqueous solution (neutralization degree: 70mol%; solid content: 45.8% by weight).
[0093] When the temperature of the water-soluble unsaturated monomer aqueous solution rises due to the heat of neutralization and reaches 40°C, the mixture is placed in a container containing 2,400 ppmw (based on the acrylic acid monomer) of sodium persulfate (SPS) as a thermal polymerization initiator, and then irradiated with ultraviolet light (irradiation dose: 10 mV / cm) for 1 minute. 2 ) and UV polymerization was carried out, followed by aging by applying heat in an oven at 80° C. for 120 seconds to obtain a hydrous gel polymer sheet.
[0094] (Step 2-1-Drying, pulverization) The obtained hydrogel polymer sheet was passed through a chopper with a hole size of 16 mm to produce a crumb. The crumb was dried in an oven capable of shifting airflow up and down. Hot air at 185°C was blown from bottom to top for 15 minutes and from top to bottom for 15 minutes to dry uniformly, so that the moisture content of the dried material after drying was 2% by weight or less. After this drying process, the product was classified using a standard mesh sieve according to the ASTM standard to obtain a base resin powder having a particle size of 150 μm to 850 μm.
[0095] (Step 2-2-Classification) Meanwhile, fine powder having a particle size of less than 150 μm generated during the process was subjected to a fine powder regranulation process to produce fine powder regranulated material (B) having a particle size of 150 μm or more. 70 wt% of the dry polymer (A) thus obtained and 30 wt% of the fine powder regranulated material (B) were pulverized using a pulverizer and classified using a standard mesh sieve according to the ASTM standard to obtain a base resin powder with a particle size distribution of #20-#30 / #30-#50 / #50-#100 / #100 or less = 22 / 64 / 13 / 1 (wt%).
[0096] (Step 3-Surface Crosslinking) Next, 100 parts by weight of the base resin powder was put into a paddle dryer, followed by adding a surface crosslinking solution containing 4.7 parts by weight of water, 0.2 parts by weight of ethylene carbonate as a surface crosslinking agent, 0.05 parts by weight of a PCE aqueous solution (Polycarboxylic acid salt type surfactant (Cas no. 381686-36-8) 45~55wt% + water 45~55wt%), and 0.3 parts by weight of an ALS aqueous solution (aluminum sulfate 23wt% + water 73wt%).
[0097] The time when the surface crosslinking solution was added was regarded as the start of surface crosslinking, and the surface crosslinking was performed for a total of 55 minutes while increasing the temperature from the initial temperature (T0) of 115 ° C. at the time of addition to the target temperature (T) of 182 ° C. After the surface crosslinking solution was added, the temperature was increased to 169 ° C. (T1) when 20 minutes had elapsed, and then the temperature was increased for 10 minutes to 182 ° C. when 30 minutes had elapsed, to perform the surface crosslinking reaction. Finally, after maintaining the temperature at 182 ° C. (T2) for 20 minutes (= 50 minutes had elapsed), the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0098] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.
[0099] Example 2 A superabsorbent resin was produced in the same manner as in Example 1, except that a base resin powder was used in which the particle size distribution of the base resin powder was adjusted to #20-#30 / #30-#50 / #50-#100 / #100 or less=30 / 55 / 13 / 2 (wt%) by adjusting the apparatus in the classification step of step 2-2 in Example 1.
[0100] Example 3 A superabsorbent resin was produced in the same manner as in Example 1, except that the temperature rise conditions were adjusted in the surface cross-linking step of step 3. Specifically, surface cross-linking was performed for 55 minutes while raising the temperature to a target temperature (T) of 179°C. At this time, the temperature was raised to 169°C (T1) over a period of 20 minutes after the surface cross-linking solution was added, and then the temperature was raised to 179°C after 30 minutes to perform the surface cross-linking reaction. Finally, after maintaining the temperature at 179°C (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0101] Example 4 A superabsorbent resin was produced in the same manner as in Example 1, except that the temperature rise conditions were adjusted in the surface cross-linking step of step 3. Specifically, surface cross-linking was performed for 55 minutes while raising the temperature to a target temperature (T) of 184°C. At this time, the temperature was raised to 169°C (T1) 20 minutes after the surface cross-linking solution was added, and then the temperature was raised to 184°C 30 minutes after the surface cross-linking reaction was performed. Finally, after maintaining the temperature at 184°C (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0102] Example 5 A superabsorbent resin was produced in the same manner as in Example 1, except that the temperature rise conditions were adjusted in the surface cross-linking step of step 3. Specifically, surface cross-linking was performed for 55 minutes while raising the temperature to a target temperature (T) of 186°C. At this time, the temperature was raised to 169°C (T1) 20 minutes after the addition of the surface cross-linking solution, and then the temperature was raised to 186°C 30 minutes after the addition of the surface cross-linking solution to perform the surface cross-linking reaction. Finally, after maintaining the temperature at 186°C (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0103] Example 6 A superabsorbent resin was produced in the same manner as in Example 1, except that in the surface crosslinking step of Step 3 of Example 1, 4.7 parts by weight of water, 0.115 parts by weight of ethylene carbonate, 0.115 parts by weight of propylene carbonate, 0.05 parts by weight of an aqueous PCE solution, and 0.3 parts by weight of an aqueous AIS solution were added to 100 parts by weight of the mixture of the base resin powder and the regranulated fine powder.
[0104] Example 7 A superabsorbent resin was produced in the same manner as in Example 1, except that the temperature rise conditions were adjusted in the surface cross-linking step of step 3. Specifically, surface cross-linking was performed for 55 minutes while raising the temperature to a target temperature (T) of 180°C. At this time, the temperature was raised to 160°C (T1) 20 minutes after the surface cross-linking solution was added, and then the temperature was raised to 180°C 30 minutes after the surface cross-linking reaction was performed. Finally, after maintaining the temperature at 180°C (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0105] Comparative Example 1 A superabsorbent resin was prepared in the same manner as in Example 1, except that the surface crosslinking temperature rise conditions were changed in the surface crosslinking step of Step 3.
[0106] The time when the surface crosslinking solution was added was regarded as the start of surface crosslinking, and surface crosslinking was performed for 55 minutes while increasing the temperature from the initial temperature (T0) of 115 ° C. at the time of addition to the target temperature (T) of 187 ° C. At this time, the temperature was increased to 159 ° C. (T1) 20 minutes after the addition of the surface crosslinking solution, and then the temperature was increased to 187 ° C. 30 minutes after the addition of the surface crosslinking solution to perform the surface crosslinking reaction. Finally, after maintaining the temperature at 187 ° C. (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0107] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.
[0108] Comparative Example 2 In the classification step of step 2-2 in Example 1, 80 wt % of the dry polymer (A) and 20 wt % of the fine regranulated powder (B) were mixed and classified to have the same particle size distribution to produce a base resin powder.
[0109] The time when the surface crosslinking solution was added was regarded as the start of surface crosslinking, and the surface crosslinking was performed for a total of 55 minutes while increasing the temperature from the initial temperature (T0) of 115 ° C. at the time of addition to the target temperature (T) of 187 ° C. At this time, the temperature was increased to 159 ° C. (T1) 20 minutes after the addition of the surface crosslinking solution, and then the temperature was increased to 187 ° C. 30 minutes after the addition of the surface crosslinking solution to perform the surface crosslinking reaction. Finally, after maintaining the temperature at 187 ° C. (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0110] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.
[0111] Comparative Example 3 A superabsorbent resin was prepared in the same manner as in Example 1, except that the surface crosslinking temperature rise conditions were changed in the surface crosslinking step of Step 3.
[0112] The time when the surface crosslinking solution was added was regarded as the start of the surface crosslinking, and the temperature was raised from the initial temperature (T0) of 115°C at the time of addition to 168°C (T1) over 30 minutes after the addition of the surface crosslinking solution, and then the temperature was lowered to 163°C (T2) over 15 minutes to carry out the surface crosslinking reaction. Finally, the temperature was lowered to 163°C (T2) for 5 minutes. f ), the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0113] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.
[0114] Comparative Example 4 A superabsorbent resin was prepared in the same manner as in Example 1, except that the surface crosslinking temperature rise conditions were changed in the surface crosslinking step of Step 3.
[0115] The time when the surface crosslinking solution was added was regarded as the start of surface crosslinking, and surface crosslinking was performed for 55 minutes while increasing the temperature from the initial temperature (T0) of 115 ° C. at the time of addition to the target temperature (T) of 182 ° C. At this time, the temperature was increased to 160 ° C. (T1) 20 minutes after the addition of the surface crosslinking solution, and then the temperature was increased to 182 ° C. 30 minutes after the addition of the surface crosslinking solution to perform the surface crosslinking reaction. Finally, after maintaining the temperature at 182 ° C. (T2) for 20 minutes, the surface-treated powder was discharged when the total residence time in the paddle dryer was 55 minutes.
[0116] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.
[0117] The properties of the superabsorbent resins produced in the above Examples and Comparative Examples were evaluated by the following methods. The results are shown in Table 1.
[0118] [Experimental Example 1] (1)Centrifuge Retention Capacity (CRC) Among the superabsorbent resins prepared in the examples and comparative examples, those having a particle size of 150 to 850 μm were selected, and the centrifuge retention capacity (CRC) was measured based on the no-load water absorption capacity according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP241.2.
[0119] Specifically, the superabsorbent resin obtained in each of the examples and comparative examples was classified with a sieve of #30-50 to obtain a resin. Such resin W0(g) (about 0.2g) was evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was drained for 3 minutes under conditions of 250G using a centrifuge, and the mass W2(g) of the envelope was measured. In addition, the same operation was performed without using the resin, and the mass W1(g) at that time was measured. Using each of the obtained masses, the CRC(g / g) was calculated according to the following formula 2.
[0120] [Formula 2] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0121] (2) Absorbency Under Pressure (AUP) The absorbency at 0.7 psi of each of the superabsorbent resins produced in the examples and comparative examples was measured by the EDANA method NWSP242.0.R2. The resin-classified powder used in the CRC measurement was used for measuring the absorbency at 0.7 psi.
[0122] Specifically, a stainless steel wire mesh of 400 mesh was attached to the bottom of a plastic cylinder with an inner diameter of 25 mm. Under conditions of room temperature and humidity of 50%, water-absorbent resin W0(g) (0.16 g) was evenly spread on the wire mesh, and a piston capable of applying a load of 0.7 psi evenly on the wire mesh was made slightly smaller than the outer diameter of 25 mm, had no gap with the inner wall of the cylinder, and was made to be capable of unhindered vertical movement. At this time, the weight W3(g) of the device was measured.
[0123] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a petroleum dish with a diameter of 150 mm, and physiological saline solution consisting of 0.9% by weight of sodium chloride was placed at the same level as the upper surface of the glass filter. A piece of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted and its weight W4 (g) was measured.
[0124] Using the obtained masses, the pressurized absorbency (g / g) was calculated according to the following formula 3.
[0125] [Formula 3] AUP(g / g)=[W4(g)-W3(g)] / W0(g)
[0126] (3) EFFC (arithmetic mean of Centrifugation Retention Capacity (CRC) and Absorbent Capacity under Pressure (AUP)) For the superabsorbent resins produced in the Examples and Comparative Examples, EFFC was calculated according to the following Equation 1.
[0127] [Formula 1] EFFC=(CRC+AUP) / 2
[0128] In the above formula 1, CRC indicates the centrifugal retention capacity (CRC) of the superabsorbent polymer measured by EDENA method WSP241.2, AUP indicates the absorbency of the superabsorbent polymer under pressure of 0.7 psi as measured by the EDANA method NWSP242.0.R2.
[0129] [Experimental Example 2] In the above examples and comparative examples, the reaction time of the surface crosslinking step in step 3 of the manufacturing process was further examined to examine the tendency of property deviation during the surface crosslinking process.
[0130] Specifically, in the surface crosslinking step 3 in the Examples and Comparative Examples, heat treatment was performed at the final temperature for 70 minutes, and the time point at which the surface crosslinking solution was added was considered to be the start time of surface crosslinking (0 minutes). 10 g samples were obtained from the surface crosslinking reactor at 40 minutes, 50 minutes, 60 minutes, and 70 minutes, respectively.
[0131] For the samples of the examples and comparative examples, those having a particle size of 150 to 850 μm were taken and the centrifuge retention capacity (CRC) based on the absorbency under no load according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP241.2 and the absorbency under pressure (AUP) at 0.7 psi according to the EDANA method NWSP242.0.R2 were measured. These were measured in the same manner as in the experimental example 1 described above.
[0132] Figure 1 shows the measured values of CRC according to the surface crosslinking reaction time. Among them, the deviation value of CRC was calculated based on 50 minutes and 60 minutes, and the results are shown in Table 1. Figure 2 shows the AUP value for CRC by surface crosslinking reaction time period.
[0133] [Table 1]
[0134] As can be seen from the data in Table 1, in the examples of the manufacturing method of the present invention, the deviation of the centrifugal water retention capacity of the superabsorbent resin particles produced by controlling the heat treatment temperature conditions in the surface crosslinking stage was reduced, and the absorbent properties of the superabsorbent resin finally produced were significantly improved. Specifically, referring to the contents of FIG. 1 together with Table 1, it was confirmed that in the examples, the deviation of CRC was significantly reduced depending on the surface crosslinking reaction time. In the cases of Comparative Examples 1 and 2, the deviation of CRC was significantly large, which indicated that the properties of the superabsorbent resin finally produced were not uniform and the CRC properties of the final product were also reduced. In the case of Comparative Example 3, the deviation of the change in CRC was large compared to the examples, and in particular, the range of AUP was very low compared to the examples, so it was confirmed that it was outside the desired absorption property range.
[0135] 2, it was confirmed that the physical properties of CRC and AUP, which are in a trade-off relationship with each other, increased in the case of the examples, while decreased in the cases of Comparative Examples 1 and 2. Meanwhile, in the case of Comparative Example 3, AUP showed a significantly low value, which means that the surface cross-linking reaction did not proceed well.
Claims
1. Step 1: forming a hydrogel polymer by cross-linking an acrylic acid monomer having at least a partially neutralized acid group in the presence of an internal cross-linking agent; Step 2: drying, pulverizing and classifying the hydrogel polymer to obtain a base resin powder; and (3) heat-treating the base resin powder in the presence of a surface cross-linking agent to prepare highly water-absorbent resin particles having a surface cross-linked layer formed thereon. The surface cross-linking agent is contained in an amount of 1,000 ppmw to 5,000 ppmw based on the base resin powder, The total time for surface crosslinking in step 3 is 45 to 75 minutes. The surface cross-linking of step 3 is carried out by increasing the temperature to a target temperature (T), The temperature (T 1 ) at the point when 90% to 100% has elapsed (T 2 ) is 12°C to 17°C.
2. The method for producing a highly water-absorbent resin according to claim 1, wherein the target temperature is 170°C to 190°C.
3. The method of claim 1, wherein the total time for performing the surface cross-linking in step 3 is 50 to 60 minutes.
4. The method for producing a highly water-absorbent resin according to claim 1, wherein the surface cross-linking agent is at least one selected from the group consisting of 1,3-propanediol, propylene glycol, 1,4-butanediol, ethylene carbonate, propylene carbonate, and ethylene glycol diglycidyl ether.
5. The method for producing a superabsorbent polymer according to claim 1, wherein the superabsorbent polymer has a centrifugation retention capacity (CRC) of 40 g / g or more as measured by EDANA method WSP241.
2.
6. The method for producing a superabsorbent polymer according to claim 1, wherein the superabsorbent polymer has an absorbency under pressure (AUP) of 18.0 g / g to 25.0 g / g at 0.7 psi according to EDANA method WSP242.0.R2.
7. The method for producing the superabsorbent polymer according to claim 1, wherein the superabsorbent polymer has an effective water absorption capacity (EFFC) of 31 g / g or more, as calculated by the following formula 1: [Formula 1] Effective absorbent capacity (EFFC) = {water retention capacity (CRC) + absorbent capacity under 0.7 psi pressure (AUP)} / 2.
Citation Information
Patent Citations
super absorbent polymer
JP2016516877A
Superabsorbent resin
JP2017517600A
Highly water-absorbent resin and method for producing the same
JP2020505477A
Manufacturing method of superabsorbent resin
JP2020516753A
Preparation method of superabsorbent polymer
US20140058048A1